Analysis of the Effects of Motivation and Work Discipline in Efforts to Improve Employee Performance at the Koja District Office - Noviherni; Dian Puspita, Cindy (JOURNAL INTELEKTUAL, 2023)
Introduction/Main Objectives: To determine the effect of motivation and work discipline on employee performance. Background Problems: Decreased performance caused by a lack of work motivation among employees because they are seen as not being optimal in terms of completing tasks given by their superiors and some jobs are monotonous which are only done repeatedly so that boredom appears and makes work motivation decrease. Novelty: Retesting the same variables by previous researchers, by analyzing different objects and subjects. Research Methods: This research uses a descriptive quantitative approach with a sample of 100 respondents and an analysis tool using SmartPLS. Finding/Results: From the research results, there is an influence of motivation and work discipline on the performance of Koja District employees in the North Jakarta area. Conclusion: Managers should pay attention to motivation and discipline in improving employee performance, that providing continuous motivation will increase performance significantly.